The application of knowledge communication system models to library information science education [soundrecording] Tefco Saracevic. - Saracevic, Tefco; Saracevic,Tefco; American Library Association. Conference (91st). (Los Angeles, Calif. CREDR Corp, 1973)
Draws on Shannon and Weaver's model of the communication process, Norman Weiner's cybernetic model, and the Goffman epidemic model of communication. Suggests viewing a library as one example of a knowledge communication system. Derives a curriculum for librarianship and information science based on it.
American Library Association, 92nd annual conference. Media: man, material, machine
Keywords: Information storage and retrieval systems -- Congresses; Library education -- Congresses; Library science; Communication